Metabolic niche differentiation and napA evolution stabilize partial denitrification in wastewater ecosystems - Jiapeng Li; Xiaotian Zuo; Linqing Qiu; Fangang Meng (Water Research, 2026)

Host proteins and symbiotic bacteria mediate the thermal response differences of the two color phenotypes of Porites lutea to extreme marine heatwaves in Weizhou Island - Yonggang Wang; Kefu Yu; Linqing Meng; Sanqiang Gong; Xiaopeng Yu; Xueyong Huang; Wen Huang (Marine Pollution Bulletin, 2026)

Prediction of in situ seafloor sediment sound speed with machine learning - Mujun Chen; Linqing Zhang; Xinfeng Hu; Xiangmei Meng; Guangming Kan; Siyou Tong; Jingqiang Wang; Guanbao Li; Baohua Liu; Qingfeng Hua; Siqi Wu; Xiaobo Zhang (Journal of Oceanology and Limnology, 2026)

Impedance inversion of high-frequency Chirp sub-bottom profiles constrained by borehole data - Linqing Zhang; Xishuang Li; Lejun Liu; Xiangmei Meng; Qingjie Zhou; Kai Liu; Qingfeng Hua; Jingqiang Wang (Marine Georesources & Geotechnology, 2026)

Antioxidant capacity is a key factor in the difference in thermal tolerance between massive Porites lutea and branching Acropora formosa - Linqing Meng; Ronghua Tan; Zunyong Xiao; Jinlian Chen; Zhihua Huang; Yonggang Wang; Enguang Yang; Yupeng Zhou; Mingpei Xu; Kefu Yu; Wen Huang (Marine Pollution Bulletin, 2025)

Sound speed prediction of seafloor sediments in the South Yellow Sea based on BP-AdaBoost model - Yiming Liang; Linqing Zhang; Wenlong Liu; Xiangmei Meng; Guangming Kan; Jingqiang Wang; Guanbao Li; Baohua Liu; Mujun Chen (Marine Georesources & Geotechnology, 2025)

High- and low-temperature stress responses of Porites lutea from the relatively high-latitude region of the South China Sea - Wen Huang; Zhihua Huang; Enguang Yang; Linqing Meng; Jinlian Chen; Ronghua Tan; Zunyong Xiao; Yupeng Zhou; Mingpei Xu; Kefu Yu (Marine Environmental Research, 2025)

Heat-tolerant subtropical Porites lutea may be better adapted to future climate change than tropical one in the South China Sea - Wen Huang; Jinlian Chen; Enguang Yang; Linqing Meng; Yi Feng; Yinmin Chen; Zhihua Huang; Ronghua Tan; Zunyong Xiao; Yupeng Zhou; Mingpei Xu; Kefu Yu (Science of The Total Environment, 2025)

Heat‐tolerant intertidal rock pool coral Porites lutea can potentially adapt to future warming - Wen Huang; Linqing Meng; Zunyong Xiao; Ronghua Tan; Enguang Yang; Yonggang Wang; Xueyong Huang; Kefu Yu (Molecular Ecology, 2024)
The growing threat of global warming on coral reefs underscores the urgency of identifying heat‐tolerant corals and discovering their adaptation mechanisms to high temperatures. Corals growing in intertidal rock pools that vary markedly in daily temperature may have improved heat tolerance. In this study, heat stress experiments were performed on scleractinian coral Porites lutea from subtidal habitat and intertidal rock pool of Weizhou Island in the northern South China Sea. Thermotolerance differences in corals from the two habitats and their mechanisms were explored through phenotype, physiological indicators, ITS2, 16S rRNA, and RNA sequencing. At the extremely high temperature of 34°C, rock pool P. lutea had a stronger heat tolerance than those in the subtidal habitat. The strong antioxidant capacity of the coral host and its microbial partners was important in the resistance of rock pool corals to high temperatures. The host of rock pool corals at 34°C had stronger immune and apoptotic regulation, downregulated host metabolism and disease‐infection‐related pathways compared to the subtidal habitat. P. lutea , in this habitat, upregulated Cladocopium C15 (Symbiodiniaceae) photosynthetic efficiency and photoprotection, and significantly increased bacterial diversity and coral probiotics, including ABY1, Ruegeria , and Alteromonas . These findings indicate that rock pool corals can tolerate high temperatures through the integrated response of coral holobionts. These corals may be ‘touchstones’ for future warming. Our research provides new insights into the complex mechanisms by which corals resist global warming and the theoretical basis for coral reef ecosystem restoration and selection of stress‐resistant coral populations.

Prediction Model of the Sound Speed of Seafloor Sediments on the Continental Shelf of the East China Sea Based on Empirical Equations - Guangming Kan; Junjie Lu; Xiangmei Meng; Jingqiang Wang; Linqing Zhang; Guanbao Li; Baohua Liu; Qingfeng Hua; Mujun Chen (Journal of Marine Science and Engineering, 2023)
Based on the data of the acoustic and physical properties of seafloor sediments obtained on the continental shelf area of the East China Sea (ECS), prediction equations of the sediment sound speed based on single and dual parameters were established, and the correlation of the sound speed with physical parameters was discussed. The results show that the sediment sound speed (c) is strongly correlated with water content (w), density (ρ), void ratio (e), mean grain size (Mz) and median grain size (Md), and the coefficient of determination R2 of the empirical regression equation is generally greater than 0.80, while the empirical regression equation coefficient of determination R2 of the compression coefficient (a) and compression modulus (E) are slightly lower, with 0.79 and 0.73, respectively. The coefficients of determination of the dual parameter regression equations between sediment sound speed with physical property parameters are generally higher than those of the single parameter equations, which are all higher than 0.90 indicating better prediction performance. The sensitivity of the physical parameters to the sound speed was analyzed, and the result shows that the sequence of sensitivity from high to low influence on sediment sound speed is void ratio, density, compressibility coefficient, median grain size and mean grain size. The prediction equations established in this study are a good extension and supplement to marine geoacoustic models and is of great significance for obtaining the acoustic properties of the seafloor sediments on the shelf of the East China Sea.

The chromatin remodeling protein BPTF mediates cell cycle, proliferation and apoptosis in porcine ovarian granulosa cells - Dayu Wang; Xinyue Lu; Yuan Jiang; Linqing Pan; Fuquan Zhu; Aochen Yu; Mingyue Zhao; Meng Yang; Jiaying Bi; Xu He; Honglin Liu; Juan Li (Theriogenology, 2023)

Reduced genetic diversity and restricted gene flow of broadcast-spawning coral Galaxea fascicularis in the South China Sea reveals potential degradation under environmental change - Wen Huang; Yinmin Chen; Qian Wu; Yi Feng; Yonggang Wang; Zhiying Lu; Jinlian Chen; Biao Chen; Zunyong Xiao; Linqing Meng; Xueyong Huang; Yan Wang; et al. (Marine Pollution Bulletin, 2023)

Research hotspots and trends in discovery of anticancer agents from algae: A 20-year bibliometric and visualized analysis based on Web of Science and CiteSpace - Kun Gao; Meng Zhang; Linqing Li; Mengting Yang; Qilin Zheng; Qiaoqiao Liu; Ruoxu Ning; Zheng Gao; Xiangyuan Deng (Algal Research, 2023)

Feasibility of growing microalgae on wastewaters collected from a vinegar plant for, concurrently, nutrient removal and biomass production - Zheng Gao; Kun Gao; Linqing Li; Mengting Yang; Pengfei Cheng; Qilin Zheng; Meng Zhang; Ruoxu Ning; Qiaoqiao Liu; Roger Ruan; Xiangyuan Deng (Algal Research, 2023)

Physical properties and in situ geoacoustic properties of seafloor surface sediments in the East China Sea - Jingqiang Wang; Guangming Kan; Guanbao Li; Xiangmei Meng; Linqing Zhang; Mujun Chen; Chenguang Liu; Baohua Liu (Frontiers in Marine Science, 2023)
Seafloor sediment acoustics is a burgeoning field of marine scientific research. In situ measurement technique is a key technique for investigating sediment acoustic properties. Establishing a correlation between in situ acoustic parameters and physical parameters is of great scientific significance for advancing the theory of seafloor acoustics. This study employed an in situ sediment acoustic measurement system to measure the sound speed and attenuation of various types of sediment, such as sand, silty sand, silty clay, and clayey silt. The results showed that in situ sound speed and attenuation were strongly curvilinear correlated with physical properties, such as wet bulk density, porosity, and mean grain size. Empirical regression relationships between in situ acoustic properties and physical properties were derived. These findings supplement the in situ measurement data of acoustic properties of seafloor sediments, compensate for the lack of an empirical relationship of in situ attenuation in previous studies, and broaden the predicting theory and method of the acoustic properties of seafloor sediments.

Lower cold tolerance of tropical Porites lutea is possibly detrimental to its migration to relatively high latitude refuges in the South China Sea - Wen Huang; Enguang Yang; Kefu Yu; Linqing Meng; Yonggang Wang; Jiayuan Liang; Xueyong Huang; Guanghua Wang (Molecular Ecology, 2022)
As high temperature stress due to climate change threatens tropical corals, cooler areas at relatively high latitudes may be potential refuges. Tolerance to low temperatures is critical in determining whether corals can successfully migrate to higher latitudes. However, the physiological and molecular adaptations that protect corals from low temperature stress are unclear. In this study, scleractinian Porites lutea samples from the tropical Xisha Islands (XS) and subtropical Daya Bay (DY) in the South China Sea were subjected to a reduction in ambient temperature from 26 to 12°C. Differences in physiological changes and gene expression were analysed. P. lutea from both XS and DY exhibited physiological bleaching under low temperature stress, and the Symbiodiniaceae density, Fv/Fm, and chlorophyll‐α content were significantly reduced. Symbiosome antioxidative stress and metabolic enzyme activity first increased and then decreased. RNA‐seq analysis showed that the host responded to low temperature stress by activating immune, apoptotic, and autophagic pathways and reducing metabolic levels. Nevertheless, Symbiodiniaceae lacked the physiological regulatory capacity to adapt to low temperatures. The lower cold tolerance of XS tropical P. lutea may attribute to lower oxidative stress resistance, lower photosynthetic capacity, worse energy supply, and higher susceptibility to bacterial and viral infections and diseases in XS corals. The difference in cold tolerance may result from genetic differences between the geographic populations and is possibly detrimental to the migration of tropical coral to relatively high latitude refuges. This study provides a theoretical basis for anthropogenically assisted coral migration as a response to global change.